Measuring, mapping, and anticipating climate gentrification in Florida: Miami and Tampa case studies. (December 2022) - Tedesco, Marco; Keenan, Jesse M.; Hultquist, Carolynne
Abstract: This article introduces an experimental methodology to identify proxy indicators that are conceptually consistent with the processes of Climate Gentrification ("CG"), in which a change in demand preferences among consumers and investors drives the increased consumption for real estate, in part, on lower measures of physical risk from climate change. Evaluated through case studies in the state of Florida, this article builds on the integration of multiple datasets concerning rental properties, evictions, and socioeconomic data, as well as environmental risk indices to build a Climate Gentrification Risk Index (CGRI). In the Miami case study, we find that the CGRI identifies a hotly contested neighborhood that is already known to be in a state of transition consistent with the processes of CG. In the Tampa case, the index highlights a district that exhibits strong metrics for the future accelerated occurrence of CG. Our findings suggest that transitional land uses and flexible zoning in low-exposure areas are key elements for attracting new development consistent with CG and offer insight into the challenges that local governments face understanding the types and rates of change that may be catalyzed in the broader urban processes of public and private sector climate adaptation in the built environment. Highlights: Provides methodology for identifying areas that are either subject to or vulnerable to climate gentrification. Highlights and discusses conceptual distinction between climate gentrification and conventional models of gentrification. Advances climate gentrification theory as a demand-side process driven by climate risk and exposure. Provides experimental evidence of demand shifts in commercial and industrial capital in high risk geographies. Spatial model highlights current climate gentrification in select areas in Miami and emerging vulnerability in Tampa.